Runting and Stunting Syndrome in Broiler Chickens: Histopathology and Association With a Novel Picornavirus. Issue 1 (January 2021) - de Oliveira, Letícia B.; Stanton, James B.; Zhang, Jian; Brown, Corrie; Butt, Salman Latif; Dimitrov, Kiril; Afonso, Claudio L.; Volkening, Jeremy D.; Lara, Leonardo J. C.; de Oliveira, Camila Stefanie F.; Ecco, Roselene
Runting stunting syndrome (RSS) in commercial chickens has been reported worldwide, and although several studies have attempted to clarify the cause and describe the lesions, there are gaps in knowledge of the epidemiology, pathogenesis, and etiology. The study objective was to use commercial chicks naturally affected by RSS to describe the histologic changes of RSS in all segments of the small intestine in chicks of different ages and to identify viral gene sequences in affected chicks and their association with histologic lesions. Chicks lacking clinical signs but from the same houses and from unaffected houses were used as controls. The average weight of affected chicks was significantly lower than expected for their flocks. Macroscopically, the small intestines had paler serosa, with watery, mucoid, or foamy contents and poorly digested food. Histologic lesions were characterized by necrotic crypts, crypt dilation, and flattening of the crypt epithelium. Histomorphometry of the intestines revealed villous atrophy especially in the jejunum and ileum. Histologic changes in other organs were not observed. Random next-generation sequencing of total RNA extracted from formalin-fixed paraffin-embedded tissues detected avian nephritis virus, avian rotavirus, and picornavirus in jejunal segments from 7-day-old chicks. No viruses were detected in the jejunum of 1-day-old chicks. Detection of picornaviral reads was significantly associated ( P < .05) with histologic lesions of RSS. Sequence analysis of the picornavirus revealed genetic similarity with the genus Gallivirus . Using in situ hybridization for galliviral nucleic acid sequences, the signal was associated with crypt lesion severity, although signal was detected both in chicks with and without RSS.